Two-year outcomes following naloxone administration by police officers or emergency medical services personnel - Lowder, Evan Marie (Criminology & public policy, 2020)
Research We conducted a retrospective, quasi-experimental study of a police naloxone program to examine individual outcomes following nonfatal overdose where either police (n = 111) or emergency medical services (n = 1,229) provided a first response and administered naloxone. Individuals who received a police response were more likely to be arrested immediately following initial dispatch and had more instances of repeat nonfatal overdose two years following dispatch; there were no differences in rearrest or death rates. Findings suggest police naloxone programs may increase short-term incarceration risk, but we found little evidence overall of long-term adverse effects. Policy Implications Naloxone is a tool to reduce fatal opioid-involved overdose. Its provision alone does not constitute a comprehensive agency response to the opioid epidemic. Findings support the need for standardized policies and procedures to guide emergency responses to nonfatal overdose events and ensure consistency across agencies.